An experimental study on improving reading comprehension and analytical writing skills of twelfth-grade students on lexical and collaborative learning in Chinese language courses - Renjie, Deng; Jarutkamolpong, Suwisa; Jantharajit, Nirat (Asian Journal of Education and Training, 2024)
This study explores the practical effects of lexical and collaborative learning on improving reading comprehension and analytical writing skills among twelfth-grade students in Chinese language classes. A sample of 30 students aged 17 to 19 was selected from a public high school in China. The Chinese Reading Comprehension Skills Test Paper (CRCSTP) and the Analytical Writing Skills Assessment Scale (AWSAS) were used to measure students' reading comprehension and analytical writing abilities before and after the experiment, employing a single-group pretest-posttest experimental design. Students' Chinese reading comprehension skills significantly improved after the experiment, with the standard deviation (SD) decreasing from 2.95 to 2.01 and the mean score (X¯) increasing from 16.67 to 18.47. The t-test indicated a substantial improvement (t(29) = -5.34, p < 0.05). Additionally, students' analytical writing abilities showed significant enhancement, with the SD decreasing from 2.34 to 1.79 and X¯ increasing from 17.2 to 20.1. The t-test demonstrated a statistically significant improvement (t(29) = -12.52, p < 0.05). These findings suggest that integrating lexical and collaborative learning into the Chinese language curriculum effectively enhances twelfth-grade students' reading comprehension and analytical writing skills.